2011
DOI: 10.1111/j.1467-9361.2010.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Destined to Receive: The Impact of Remittances on Household Decisions in Armenia

Abstract: The paper uses data from Armenia to test the implications of remittance flows on behavior of receiving households. We find that remittance-receiving households work fewer hours and spend less on the education of their children. While saving more, these households are not leveraging their savings to borrow from the banking system to expand their business activities. This evidence suggests that the benefits of remittances might be overstated and emphasizes the importance of measuring their impact in a general-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 22 publications
4
45
0
Order By: Relevance
“…Hildebrandt and McKenzie (2005) found positive effects of parental emigration on children's health in Mexico. As regards the emigration of spouses, Grigorian and Melkonyan (2011) found that the emigration of a spouse tended to reduce the labour supply of the spouse left behind.…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…Hildebrandt and McKenzie (2005) found positive effects of parental emigration on children's health in Mexico. As regards the emigration of spouses, Grigorian and Melkonyan (2011) found that the emigration of a spouse tended to reduce the labour supply of the spouse left behind.…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…Although there are some studies on the role of remittances in European countries (Leon-Ledesma and Piracha, 2001;Schiopu and Siegfried, 2006;Grigorian and Melkonyan, 2011, and many more), only a few studies focused on the remittances and using the microlevel survey data on the ASEAN countries (Parinduri and Thangavelu, 2011;Nguyen and Purnamasari, 2011) failed to capture the fate of return migrants in this region. Given that many countries worldwide tend to recognise international work contracts and labour migration, return migration today becomes an important phenomenon in the world and in the ASEAN region in particular, so the home countries should enact the policies to capture their skills, knowledge, and savings for the aims of further alleviation of poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Thus while men are traditionally expected to support the family, household management in Armenia is generally a woman's domain. Such an expectation in a society with a poor economy which has led to male labor migration (eg Gevorkyan & Mashuryan 2006;Grigorian & Melkonyan 2011), can only increase females' responsibilities in taking care of the family. Such a situation could be exacerbated by an unemployment rate of 41.5% among females (and 31.8% among males) ages 15-24 (The World Factbook 2014), making it more likely to facilitate serial viewing as a way to pass the time in general and among females in particular.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 2013 (the year when the present survey was conducted), the poverty rate in Armenia was 32.0%, and it was higher in rural areas (27.5%) than in Yerevan (20.1%); and the unemployment rate was 17% (The World Bank 2016). The dire economic situation has led to male labor migration (Gevorkyan & Mashuryan 2006;Grigorian & Melkonyan 2011), posing a 'threat to [their] existential security' (Payaslian 2011, p. 21). The debilitating impact of these harsh economic realities on Armenian social life has been elucidated in qualitative research studies (Tholen et al 2012).…”
Section: The Republic Of Armenia and Soap Operas: A Brief Historymentioning
confidence: 99%